Structured soil mixture in Geobags for Geobarrier system - Chua, Yuan Shen (Nanyang Technological University, 2022)
The Geobarrier System (GBS) is a three-layered cover system comprising a vegetative layer combined with a capillary barrier system, which harnesses the distinct difference in unsaturated hydraulic properties between a non-cohesive fine-grained layer and a coarse-grained layer to minimize the infiltration of rainwater into the underlying soil that is being protected. The vegetative layer consists of a geobag filled with approved soil mixture (ASM), which is called planting geobag. Previous research works indicated that GBS could be used as an earth retaining structure and slope stabilization system against rainfall-induced slope failures. However, the differential settlement was observed along the planting geobag in the previous study. This happened since the approved soil mixture (ASM) within the planting geobag could not be highly compacted in order to accommodate the subsistence of roots from vegetation within the ASM layers. Therefore, the objective of this study is to investigate the appropriate modification of ASM in order to reduce the deformation of the planting geobag. This study also assessed the performance of the recycled concrete aggregate (RCA) mixed with ASM to improve the sustainability aspect of the GBS. The research works involved the mixing of ASM with different percentages of RCA (called structured soil mixture or SSM) to improve the modulus elasticity of ASM layer within the planting geobag. The scope of works in this study include the experimental works in laboratory, numerical analyses and field testing. The laboratory testing consisted of index properties, soil-water characteristic curve and saturated shear strength testing as well as determination of the unsaturated permeability and the unsaturated shear strength of the ASM and SSM. The field testing consisted of the physical loading test to explore the suitable dimension of the planting geobag and the appropriate compositions of SSM which produced minimum deformation. The numerical analyses consisted of the transient finite element seepage analyses using Seep/W to evaluate the performance of the GBS incorporating the SSM in minimizing rainwater infiltration and the deformation analyses using Sigma/W to evaluate the results from loading tests. The results from the laboratory tests indicated that coarse RCA can be used to replace natural aggregate for the SSM. The results from the loading test and numerical analyses indicated that the SSM with a ratio of 50% ASM and 50% coarse RCA can be used to improve the planting geobag from the excessive deformation.